Toxicity Test of Bulk Cooking Oil with the Addition of Shallot Powder on the Blood Cytology of Mice - Fardani, Roushandy Asri; S, Dhika Juliana; Ningty, Sarly Sapty (Jurnal Biologi Tropis, 2025)
The use of bulk cooking oil added with shallot powder has no known effect on the body so it is necessary to conduct a study to determine the effect of the addition of shallot powder as a natural antioxidant added to bulk cooking oil in mice on one of the qualitative benchmark parameters in the form of cytological examination of blood. This study aims to find out about the effect of bulk cooking oil added with antioxidants, namely shallot powder on the cytological picture of the blood of mice (Mus musculus) whose analysis results are compared with bulk cooking oil added with synthetic antioxidant BHT and bulk cooking oil without the addition of antioxidants. Toxicity test was determined by blood cytology examination by looking at several parameters, namely erythrocyte morphology, erythrocyte count, leukocyte count and diff count. The results of 1-way Anova test statistical data show that there is no effect of giving onion powder in bulk cooking oil to mice (Mus musculus) on the number of erythrocytes and leukocytes. While in the diff count, the results of the Paired Sample t-test statistical data show that there is an effect of adding onion powder to bulk cooking oil in mice (Mus musculus), namely an increase in lymphocytes and neutrophil segments.